Factors Influencing Stigma to Lesbian, Gay, Bisexual, and Transgender (LGBT) Among Teenagers at Ngaran Village, Gamping, Sleman, Indonesia - Astuti, Dhesi Ari; Kurniati, Nurul (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Lesbian, Gay, Bisexual, and Transgender (LGBT) still becomes a social, theological, and psychological problem. Similar to trauma, low selfacceptance, low self-esteem, and anxiety, if it is not handled properly, the condition will be getting worse.Aims: The objective of this study is to increase prevention efforts toward stigma to the LGBT, a growing phenomenon on the teenagers.Methods: This is a quantitative study with one group pretest and posttest design. The work involved forty one (41) teenagers at at Ngaran Village, Balecatur, Gamping, Sleman, Indonesia. A set of questionnaires that has been tested for validity and reliability was given to the respondents to measure knowledge, attitude, perception, service access, and also peer's attitude to LGBT. Counseling was given once together with material content about LGBT awareness in family. Statistical analysis was employed to process and analyze the data.Results: The result showed the factors correlated to stigma about LGBT on teenagers such as knowledge, attitude, perception, access to any service, and peer's attitude. The study noticed the knowledge to LGBT (p value < 0.001) and peers' attitude (p value = 0.02) strongly build stigma among the teenagers.Conclusion: The most influencing factor of the stigma on LGBT is knowledge and peer attitudes. Involving peers in improving teenagers' knowledge and better understanding to the phenomenon are necessary to suppress discrimination and negative stigma to the LGBT people. Received: 6 February 2018, Reviewed: 12 February 2018, Received in revised form: 16 June 2018, Accepted: 27 June 2018. DOI: https://doi.org/10.35898/ghmj-22192